THE EFFECTIVENESS OF DISTRIBUTION OF SUBSIDIZED SHARIA MORTGAGE OF BANK BTN SHARIAH FOR COMMUNITIES WITH LOW INCOME: A CASE STUDY IN KENDAL REGENCY - Hening Pratika Nila Hapsari; Mahfud Nugroho (IAIN Surakarta, 2021)
This study intends to examine the procedures and mechanisms for disbursing subsidized sharia mortgage, as well as the effectiveness of subsidized mortgage distribution at BTN shariah in providing decent housing for low-income people. This study was conducted in BTN Shariah of Kendal Branch. This study used quantitative research by distributing questionnaires to 90 respondents determined through the Slovin method. To investigate the effectiveness of the distribution of subsidized mortgages, the Artificial Neuron Network (ANN) was used. The results showed that the procedures and mechanisms for disbursement of the subsidized mortgage at BTN Shariah of Kendal Branch were following the Standard Operating Procedures (SOP) that had been established by BTN Shariah. However, there was a mismatch between the Regulation of the Minister of The Ministry of Public Works and Housing No. 48/PRT/M/2015 Article 20 paragraph (7) concerning the disbursement of subsidized funds. The results of the questionnaire shower 50.5% of customers chose â€œuncertainâ€ on the indicator of â€œtimeliness of subsidies disbursementâ€ since they thought that the timing of the funds was uncertain. This statement is not in line with the regulation of the Minister for Public Works and Human Settlements that the disbursement is no later than two working days after the documents are received. Meanwhile, based on the results of calculations using the ANN, the distribution of subsidized mortgages has been effective by 0.877 or 87.7%.